Respostas fisiológicas de matrinxã (Brycon cephalus) arraçoadas com diferentes níveis de vitamina C e submetidos à exposição aérea - Abreu, Janessa Sampaio de [UNESP] (2003)
This work evaluated the participation of vitamin C on physiological responses of matrinxã (Brycon cephalus) submitted to air exposure. In the first experimental phase, 900 fish (70.15g) were random1y distributed in fifteen 500L boxes (60 fish/box) and fed 5• experimental rations (treatments): Control (no addition); TIOO (100 mg); T200 (200 mg); T400 (400 mg) and T800 (800 mg of vitamin C/ kg ration). Each ration was offered to fish from 3 boxes during 60 days and, after that, the second phase began. The experiment was divided in 3 steps, each one was considered a block (repetition) and samplings were carried out in different days. In each sampling, 28 fish of each treatment were transferred to 100 L plastic boxes (4 boxes/treatment, 7 fish/box), where they stayed for 48 hours until the stressful factor application, that consisted in taking out all fish of boxes, with polyethylene nets previously adapted to the boxes, maintaining them out of the water for two minutes. The samplings were carried out 5, 15, 30 and 60 min after they return to the water. Each sampled box was removed of the experiment to avoid additional stress. Blood were collected for glucose, cortisol, total protein, sodium, chloride, calcium determination, hematocrit, hemoglobin and white and red cells count and liver for hepatosomatic index (HSI calculation and glycogen determination. No significant differences in the cortisol, chloride, total protein, hemoglobin, leukocytes, glycogen and HSI values were registered. The blood glucose decreased, in all treatments, at 15 and 30 min at 60 min it surpassed the levels registered in first sampling (5 min.). The TI00fish showed, in all sampling times, blood glucose significantly elevated when compared to fish fed of control, T200- and T800. The serum calcium in T800 fish was larger than those 01' the control and T100 fish and the levels were significantly smaller at 30 and 60 min when compared to those registered at 5 min ...